Study into the rolling of a double-layered powdered core in a metallic sheath - Gribkov, Eduard; Berezshnaya, Olena; Hurkovskaya, Svetlana; Malyhina, Svetlana (Eastern-European Journal of Enterprise Technologies, 2018)
We have developed an analytical model of the stressed-strained state of the two-layered powdered core in a metal sheath in the deformation zone when fabricating a composite material by rolling. Based on the constructed mathematical model, we performed a theoretical analysis of the influence of starting parameters on the course of the process of rolling a composite material. By using a finite element method, we simulated the process of rolling diverse powders in a metal sheath. The result of the theoretical research is the established effect of a material and the thickness of a sheath on the geometrical characteristics of a deformation site, as well as the influence of an asymmetry factor on a change in the zone of plastic shape alteration and the density of a powdered material. We have determined the distributions of normal contact stresses and relative density over a deformation site under different clamping. We calculated the components of rolling forces under deformation of a powdered core and a metal sheath. It was established that an increase in the thickness of a sheath leads to an increase in energy-force parameters of the process. In this case, the component of a rolling force due the sheath deformation can be both comparable to the component from the deformation of a powdered core, and exceed it by several times. The undertaken experimental study into the process has confirmed the validity of the constructed mathematical model that could be applied for determining the optimal technological regimes for rolling a 2-layer powdered core in a metal sheath. A technology for rolling a 2-layer powdered core in a metal sheath has been proposed, which includes rolling in two runs, filling the metal sheath consistently with components. It was established that at rolling based on the proposed technology the core’s relative density increases under the same rolling modes. In this case, the size of a powder’s fraction is retained, which is a prerequisite for a given production technology